The Influence of Organizational Culture and Job Satisfaction on Employee Performance at PT. Asri Pancawarna - Nurlita Octaviani; Aji Tuhagana; Zenita Apriani (International Journal of Economics and Management Research, 2025)
This research is motivated by the importance of improving employee performance at PT. Asri Pancawarna, considering that there is still inequality in the quality and quantity of work results. Organizational culture and job satisfaction are suspected to be factors that influence employee performance. This study uses a quantitative approach with descriptive and verification methods, and data collection is carried out through observation, interviews, and distribution of Likert-based questionnaires to employees. Data were analyzed using multiple linear regression methods with the help of SPSS version 30 software. The results of the study indicate that organizational culture and job satisfaction together affect employee performance. Separately, job satisfaction is proven to have a stronger influence on performance, while organizational culture does not have a significant influence individually. The discussion reveals that managing job satisfaction, such as providing fair compensation, promotion transparency, and improving working conditions, are key to improving employee performance. In conclusion, companies need to prioritize efforts to improve job satisfaction to encourage better employee performance.